The Magician - Scott, Michael (New York : Ember, 2008)
After fleeing Ojai, Nicholas, Sophie, Josh, and Scatty emerge in Paris, the City of Lights. Home for Nicholas Flamel. Only this homecoming is anything but sweet. Perenell is still locked up back in Alcatraz and Paris is teeming with enemies. Nicollo Machiavelli, immortal author and celebrated art collector, is working for Dee. He's after them, and time is running out for Nicholas and Perenell. For every day spent without the Book of Abraham the Mage, they age one year--their magic becoming weaker and their bodies more frail. For Flamel, the Prophesy is becoming more and more clear. It's time for Sophie to learn the second elemental magic: Fire Magic. And there's only one man who can teach it to her: Flamel's old student, the Comte de Saint-Germain--alchemist, magician, and rock star. Josh and Sophie Newman are the world's only hope--if they don't turn on each other first.
Keywords: ALCHEMISTS